Implications of the current trend in mortgage valuation practice in Nigeria - Aluko, Bioye Tajudeen (International Journal of Strategic Property Management, 2010)
The emerging concern on the reliability of property valuations coupled with the attendant consequences of growing number of distressed banks in Nigeria necessitate this study. Therefore, the study examined the mortgage valuation process including sources of valuation instructions, bases and methods being adopted and their implications on lending decisions and valuation profession in the study area. To accomplish the study, questionnaires were randomly administered on samples of estate surveying and valuation firms and lending institutions respectively in Lagos Metropolis. The data emanating there from were analysed using frequency distributions, ranking mean and relative important index ranking. The study, prima facie, established that mortgage valuation has been an important input in lending decisions. It further showed the implications of the blind adoption of the cost approach, inconsistency amongst valuers and non – inclusion of insurance valuation in the mortgage valuation process.First published online: 18 Oct 2010